DETERMINAN PENENTU KENAIKAN RETURN SAHAM PADA PERUSAHAAN TRANSPORTASI DI INDONESIA - Arum Puspita Sari; Ana Kadarningsih (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This research is intended to prove the effect of PER, DER and EPS on stock returns. The population in this study are non-manufacturing companies in the transportation sector with 21 companies with a sampling technique with certain criteria. The sample criterion is to have a complete stock return report that has been registered on IDX, the research sample is 126 of 21 companies times 6 years of financial reports listed on the IDX. The data analysis technique used in this study was a quantitative method using descriptive analysis and multiple linear regression analysis, as well as classical assumption tests as a prerequisite for multiple linear regression tests using SPSS software. The results showed that PER (Price earning ratio) did not have a positive and significant effect on Stock Returns, DER (Debt to equity ratio) did not have a positive and significant effect on Stock Returns and EPS (Earning per share) had a positive and significant effect on Stock Returns in manufacturing companies in the transportation sub-sector listed on the IDX for 2017- 2022.